Aluminum alloy sleeve and manufacturing method and application thereof

By optimizing the chemical composition and process flow of aluminum alloy casing, combined with jet deposition technology and multi-stage heat treatment, the problem of difficult to achieve both strength and corrosion resistance of aluminum alloy casing is solved, and the unity of high strength and good corrosion resistance is achieved.

CN119876709APending Publication Date: 2025-04-25CHINA NAT PETROLEUM CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311376567.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-23
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

While ensuring strength, existing aluminum alloy sleeves are difficult to improve corrosion resistance, and there is a contradiction between strength and corrosion resistance.

Method used

By optimizing chemical compositions, including Zn: 7.6% to 8.4%, Mg: 1.8% to 2.3%, Cu: 2.0% to 2.6%, Zr: 0.08% to 0.25%, Cr≤0.04%, Mn≤0.05%, Ti≤0.06%, combined with jet deposition technology and multi-stage heat treatment process, an aluminum alloy casing with high strength and good corrosion resistance was prepared.

Benefits of technology

It realizes the unity of high strength, toughness and corrosion resistance of aluminum alloy casing, significantly improves the overall performance of the material, and has a simple process and controllable cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004508206870000011
    Figure HDA0004508206870000011
Patent Text Reader

Abstract

The invention discloses an aluminum alloy sleeve and a manufacturing method and application thereof, and the aluminum alloy sleeve comprises the following components in percentage by weight: 7.6%-8.4% of Zn, 1.8%-2.3% of Mg, 2.0%-2.6% of Cu, 0.08%-0.25% of Zr, less than or equal to 0.04% of Cr, less than or equal to 0.05% of Mn, less than or equal to 0.06% of Ti, and the balance of Al and inevitable impurities. The main alloy elements Zn and Mg can greatly improve the strength of the alloy, and the Cu element can improve the stress corrosion resistance of the alloy. Microalloy elements such as Mn, Cr, Zr and Ti are mainly used for refining alloy grains, inhibiting recrystallization, improving the plasticity and toughness of the alloy and improving the corrosion resistance of the alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of petroleum pipe manufacturing, and relates to an aluminum alloy casing and a manufacturing method and application thereof. Background Art

[0002] The goal of oil and gas exploration and development in my country has gradually shifted to deep, ultra-deep and unconventional oil and gas reservoirs, and a large number of deep wells, ultra-deep wells and extended displacement wells have emerged. The main deformation forms of casing are shear deformation and crushing deformation. Studies have shown that reducing the ovality can improve the casing's anti-crushing ability. Different from the processing method of steel casing, the aluminum alloy casing obtained by extrusion has better ovality, which can improve the casing's anti-crushing ability. The aluminum alloy casing has high specific strength, which can significantly reduce the weight of the casing string, relieve stress concentration, and increase the maximum insertion depth of the casing string. In addition, the aluminum alloy casing has good high temperature resistance, which can extend the service life of the casing string and reduce safety accidents caused by casing failure in oil and gas wells.

[0003] my country's deep onshore strata will be an important area for future oil and gas development. As the mining depth increases and the mining environment becomes more demanding, higher requirements are placed on the strength and corrosion resistance of aluminum alloy casings. The strength and corrosion resistance of aluminum alloys have always been a contradictory relationship. The strength of aluminum alloys can be improved by increasing the content of alloying elements, but the toughness and stress corrosion resistance of the alloy will be reduced. By optimizing the aging treatment process, the grain boundary precipitation phase of the alloy is discontinuously distributed, which can improve the material's stress corrosion resistance, but it will sacrifice some strength. Therefore, how to improve the corrosion resistance of aluminum alloy casings while ensuring strength is a major problem that needs to be solved. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention provides an aluminum alloy casing and a manufacturing method and application thereof, thereby solving the technical problem in the prior art that the strength and corrosion resistance of the aluminum alloy casing cannot be achieved at the same time.

[0005] The present invention is achieved through the following technical solutions:

[0006] An aluminum alloy sleeve comprises, by weight percentage, Zn: 7.6%-8.4%, Mg: 1.8%-2.3%, Cu: 2.0%-2.6%, Zr: 0.08%-0.25%, Cr≤0.04%, Mn≤0.05%, Ti≤0.06%, and the balance is Al and unavoidable impurities.

[0007] Preferably, the aluminum alloy casing has a tensile strength of not less than 630 MPa, a yield strength of 550-610 MPa, and an elongation of not less than 10.0%; after heat exposure at 120°C for 500 hours, the yield strength of the aluminum alloy casing is not less than 385 MPa.

[0008] The above-mentioned method for preparing an aluminum alloy casing comprises the following steps:

[0009] S1: preparing the raw materials according to their weight percentage and preparing the tube blank through a spray deposition process;

[0010] S2: subjecting the obtained tube blank to a first stage heat treatment and a second stage heat treatment in sequence to obtain a tube blank subjected to a double-stage homogenization treatment, wherein the temperature of the first stage heat treatment is lower than the temperature of the second stage heat treatment;

[0011] S3: Extruding the tube blank that has undergone the double-stage homogenization treatment to obtain an extruded tube blank;

[0012] S4: subjecting the extruded tube to a third heat treatment and a fourth heat treatment in sequence to obtain a tube that has undergone a solid solution treatment; wherein the temperature of the third heat treatment is lower than the temperature of the fourth heat treatment;

[0013] S5: subjecting the solution treated tube blank to first, second and third stage heat treatments in sequence to obtain the aluminum alloy casing; the temperatures of the first and third stage heat treatments are both lower than the temperature of the second stage heat treatment.

[0014] Preferably, in step S2, the temperature of the first stage heat treatment is 400-415° C., and the heat preservation time is 8-12 hours; the temperature of the second stage heat treatment is 455-470° C., and the heat preservation time is 12-24 hours.

[0015] Preferably, in step S2, the heating rates during the first stage heat treatment and the second stage heat treatment are both 10-20°C / min.

[0016] Preferably, during the variable cross-section extrusion process, the extrusion ratio is greater than 18 and the extrusion speed is 30 mm / min; before the variable cross-section extrusion process, the tube blank that has undergone double-stage homogenization treatment is heated to 390-420°C, and the variable cross-section extrusion process is performed after keeping the temperature for 20 minutes.

[0017] Preferably, in step S4, the temperature of the third stage heat treatment is 450-460° C., and the temperature is kept at 1-2 hours. The temperature of the fourth stage heat treatment is 470-480° C., and the temperature is kept at 1-1.5 hours.

[0018] Preferably, the heating rates of the third stage heat treatment and the fourth stage heat treatment are both greater than 20°C / min.

[0019] Preferably, in step S5, the first stage heat treatment temperature is 105-120°C, and the heat preservation is 24 hours; the second stage heat treatment temperature is 180-190°C, and the heat preservation is 0.5-1 hour; the third stage heat treatment temperature is 120°C and the heat preservation is 24 hours.

[0020] The above-mentioned aluminum alloy casing is used in the field of oil and gas exploration and development.

[0021] Compared with the prior art, the present invention has the following beneficial technical effects:

[0022] The invention discloses an aluminum alloy casing, which comprises, by weight percentage, Zn: 7.6% to 8.4%, Mg: 1.8% to 2.3%, Cu: 2.0% to 2.6%, Zr: 0.08% to 0.25%, Cr≤0.04%, Mn≤0.05%, Ti≤0.06%, and the balance is Al and inevitable impurities. In the invention, the main alloy elements Zn and Mg can greatly improve the strength of the alloy, and the Cu element can improve the stress corrosion resistance of the alloy. The main functions of the microalloying elements Mn, Cr, Zr, Ti, etc. are to refine the alloy grains, inhibit recrystallization, improve the alloy plasticity, toughness and improve the corrosion resistance of the alloy. The invention controls Zn / Mg at 3.3-4.67, Cu / Mg at 0.87-1.44, adds trace element Zr, controls the contents of impurity elements Fe and Si, and combines a suitable heat treatment process to obtain an alloy structure in which a micron crystalline phase formed by solidification, a submicron or nanometer dispersed phase precipitated by high temperature, and a nanometer metastable phase precipitated by aging are dispersedly distributed on an Al matrix.

[0023] In addition, the present invention also discloses a method for preparing an aluminum alloy sleeve, wherein a tube blank is prepared by spray deposition technology, so that the Zn content in the alloy reaches more than 8% without causing serious segregation, thereby improving the strength of the alloy. In addition, due to the high cooling rate of spray forming, the composition of the obtained deposited blank is uniform and the grains are fine. The second phase is distributed in a semi-continuous network at the grain boundary, while the 1-5 μm spherical or short rod-shaped second phase is dispersed in the crystal. The overall distribution is relatively uniform, and the composition of the second phase at the grain boundary is similar to that of the second phase in the crystal. A two-stage homogenization treatment process is adopted, which, on the one hand, promotes the coarse AlZnMgCu primary phase to dissolve back into the matrix to the maximum extent, so as to reduce the difficulty of subsequent solution heat treatment, and at the same time avoids excessive heating temperature causing grain boundary melting and overburning. On the other hand, the first stage heat treatment adopts a lower treatment temperature to promote the precipitation of fine and dense Al3Zr nuclei in the alloy. The second stage heat treatment greatly eliminates the microsegregation in the matrix, promotes the growth of Al3Zr nuclei, and forms more and more uniformly distributed Al3Zr particles, thereby inhibiting the alloy recrystallization behavior in subsequent hot working and solution treatment, and improving the strength and toughness of the alloy. In the two-stage solution treatment process, the temperature of the third stage heat treatment is kept below the eutectic temperature for a period of time to fully dissolve some strengthening phases. The temperature of the fourth stage heat treatment is higher. On the premise of avoiding overburning of the structure, it is kept at a higher temperature for a shorter time to further dissolve other strengthening phases and increase the solubility of solute atoms. This can shorten the solution time, reduce energy consumption, and improve the solution efficiency. Finally, the regression re-aging treatment (RRA treatment) is adopted, which includes three stages: the first stage is peak aging at a lower temperature, and fine coherent or semi-coherent dispersed phases are precipitated in the crystal, and coarser continuous chain particles are distributed at the grain boundaries. In the second stage, short-term regression is carried out at a higher temperature. After the regression treatment, the coherent or semi-coherent precipitates in the crystal are dissolved into the solid solution, and the continuous chain precipitates on the grain boundary merge and aggregate, and are no longer continuously distributed. This grain boundary structure improves the resistance to stress corrosion and exfoliation corrosion, but the dissolution of the η′ phase in the crystal greatly reduces the strength of the alloy. In the third stage, re-aging is carried out at a lower temperature to reach the peak strength. Small partial coherent η′ phases are precipitated in the crystal and dispersedly distributed, and the grain boundaries are still discontinuous non-coherent precipitates. After RRA treatment, the following structure is formed in the alloy: a large number of fine η′ phase particles are dispersed in the crystal, and coarse η phase precipitates are discretely distributed at the grain boundaries, accompanied by a narrow grain boundary non-precipitation zone. This structure combines the advantages of peak aging and over-aging, so that the alloy obtains the unity of high strength and good corrosion resistance. This technology can significantly improve the strength, toughness and corrosion resistance of the material, and the process is simple and the cost is controllable. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0025] Figure 1 The present invention is a schematic diagram of a process for preparing an aluminum alloy casing. DETAILED DESCRIPTION

[0026] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0027] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0028] Herein, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0029] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0030] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0031] The present invention provides an aluminum alloy casing, characterized in that, by weight percentage, it includes Zn: 7.6%-8.4%, Mg: 1.8%-2.3%, Cu: 2.0%-2.6%, Zr: 0.08%-0.25%, Cr≤0.04%, Mn≤0.05%, Ti≤0.06%, and the balance is Al and inevitable impurities, wherein the inevitable impurities include Fe and Si, preferably, Fe≤0.15%, Si≤0.10%.

[0032] The invention discloses an aluminum alloy casing, which comprises, by weight percentage, Zn: 7.6% to 8.4%, Mg: 1.8% to 2.3%, Cu: 2.0% to 2.6%, Zr: 0.08% to 0.25%, Cr≤0.04%, Mn≤0.05%, Ti≤0.06%, and the balance is Al and inevitable impurities. In the invention, the main alloy elements Zn and Mg can greatly improve the strength of the alloy, and the Cu element can improve the stress corrosion resistance of the alloy. The main functions of the microalloying elements Mn, Cr, Zr, Ti, etc. are to refine the alloy grains, inhibit recrystallization, improve the plasticity and toughness of the alloy, and improve the corrosion resistance of the alloy. The tensile properties of the aluminum alloy casing in the invention are as follows: the tensile strength is not less than 630MPa, the yield strength is 550 to 610MPa, and the elongation is not less than 10.0%; the yield strength of the aluminum alloy casing after heat exposure at 120°C for 500h is not less than 385MPa.

[0033] The test process of the tensile properties of the above-mentioned aluminum alloy casing and the yield strength of the aluminum alloy casing after heat exposure at 120°C for 500 hours is based on "GB / T 228.1-2021 Tensile test of metal materials Part 1: Room temperature test method".

[0034] In addition, if Figure 1 As shown, the present invention also discloses a method for preparing the above-mentioned aluminum alloy casing, comprising the following steps:

[0035] S1: preparing the raw materials according to their weight percentage and preparing the tube blank through a spray deposition process;

[0036] S2: Double-stage homogenization treatment: The obtained tube blank is subjected to the first-stage heat treatment and the second-stage heat treatment in sequence, and then naturally cooled to room temperature to obtain a tube blank subjected to double-stage homogenization treatment, wherein the temperature of the first-stage heat treatment is lower than the temperature of the second-stage heat treatment; wherein the temperature of the first-stage heat treatment is 400-415°C, and the temperature is kept for 8-12 hours, and the temperature of the second-stage heat treatment is 455-470°C, and the temperature is kept for 12-24 hours. The heating rates during the first-stage heat treatment and the second-stage heat treatment are both 10-20°C / min.

[0037] S3: Extrusion treatment: The tube billet after the double-stage homogenization treatment is heated to 390-420°C, kept at this temperature for 20 minutes, and then subjected to variable cross-section extrusion treatment. During the variable cross-section extrusion treatment, the extrusion ratio is greater than 18, and the extrusion speed is 30 mm / min.

[0038] S4: Two-stage solid solution treatment: The extruded tube is sequentially subjected to the third stage heat treatment and the fourth stage heat treatment, and then cooled by water spray at a cooling rate of 30-50°C / s to obtain a tube that has been solid solution treated; the temperature of the third stage heat treatment is lower than the temperature of the fourth stage heat treatment; the temperature of the third stage heat treatment is 450-460°C, and the temperature is kept for 1-2h, and the temperature of the fourth stage heat treatment is 470-480°C, and the temperature is kept for 1-1.5h. The heating rates of the third stage heat treatment and the fourth stage heat treatment are both greater than 20°C / min.

[0039] S5: Retrogression and re-aging (RRA): The solution treated tube is sequentially subjected to the first, second and third stage heat treatments to obtain the aluminum alloy casing; the temperatures of the first and third stage heat treatments are lower than the temperature of the second stage heat treatment. Specifically: keep warm at 105-120°C for 24 hours, cool to room temperature and heat to 180-190°C for 0.5-1 hour, cool to room temperature and then heat to 120°C for 24 hours. That is, the first stage heat treatment temperature is 105-120°C, kept warm for 24 hours, the second stage heat treatment temperature is 180-190°C, kept warm for 0.5-1 hour, and the third stage heat treatment temperature is 120°C for 24 hours.

[0040] The method uses spray deposition technology to prepare tube blanks, so that the Zn content in the alloy reaches more than 8% without serious segregation, thereby improving the strength of the alloy. In addition, due to the high cooling rate of spray forming, the composition of the deposited blank is uniform and the grains are fine. The second phase is distributed in a semi-continuous network at the grain boundary, while the 1-5μm spherical or short rod-shaped second phase is dispersed in the crystal. The overall distribution is relatively uniform, and the composition of the second phase at the grain boundary is similar to that of the second phase in the crystal. The two-stage homogenization treatment process is adopted. On the one hand, the coarse AlZnMgCu primary phase is maximally dissolved in the matrix to reduce the difficulty of subsequent solution heat treatment, while avoiding excessive heating temperature that causes grain boundary melting and overburning. On the other hand, the first stage heat treatment adopts a lower treatment temperature to promote the precipitation of fine and dense Al3Zr nuclei in the alloy. The second stage heat treatment greatly eliminates the microsegregation in the matrix, promotes the growth of Al3Zr nuclei, and forms more and more uniformly distributed Al3Zr particles, thereby inhibiting the alloy recrystallization behavior in subsequent hot working and solution treatment, and improving the strength and toughness of the alloy. In the two-stage solution treatment process, the temperature of the third stage heat treatment is kept below the eutectic temperature for a period of time to fully dissolve some strengthening phases. The temperature of the fourth stage heat treatment is higher. On the premise of avoiding overburning of the structure, it is kept at a higher temperature for a shorter time to further dissolve other strengthening phases and increase the solubility of solute atoms. This can shorten the solution time, reduce energy consumption, and improve the solution efficiency. Finally, the regression re-aging treatment (RRA treatment) is adopted, which includes three stages: the first stage is peak aging at a lower temperature, and fine coherent or semi-coherent dispersed phases are precipitated in the crystal, and coarser continuous chain particles are distributed at the grain boundaries. In the second stage, short-term regression is carried out at a higher temperature. After the regression treatment, the coherent or semi-coherent precipitates in the crystal are dissolved into the solid solution, and the continuous chain precipitates on the grain boundary merge and aggregate, and are no longer continuously distributed. This grain boundary structure improves the resistance to stress corrosion and exfoliation corrosion, but the dissolution of the η′ phase in the crystal greatly reduces the strength of the alloy. In the third stage, re-aging is carried out at a lower temperature to reach the peak strength. Small partial coherent η′ phases are precipitated in the crystal and dispersedly distributed, and the grain boundaries are still discontinuous non-coherent precipitates. After RRA treatment, the following structure is formed in the alloy: a large number of fine η′ phase particles are dispersed in the crystal, and coarse η phase precipitates are discretely distributed at the grain boundaries, accompanied by a narrow grain boundary non-precipitation zone. This structure combines the advantages of peak aging and over-aging, so that the alloy obtains the unity of high strength and good corrosion resistance. This technology can significantly improve the strength, toughness and corrosion resistance of the material, and the process is simple and the cost is controllable.

[0041] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0042] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0043] Zn: 7.6%~8.4%, Mg: 1.8%~2.3%

[0044] Zn and Mg elements exist mainly in the alloy as η (MgZn2) phase. The solubility of η phase in the alloy decreases rapidly with the decrease of temperature. The solubility of MgZn2 phase at eutectic temperature is 28%, and its solubility at room temperature is only 4-5%. η phase has a strong aging strengthening effect. In addition, Zn, Mg and Al can form a ternary T (Al2Mg3Zn3) phase, which has a strong aging strengthening ability. Therefore, the content of Zn and Mg elements in the alloy is the main factor determining the strength of the alloy. Increasing the content of Zn and Mg elements can greatly improve the strength of the alloy, but high content of Zn and Mg elements also reduces the toughness and stress corrosion resistance of the alloy. The Zn / Mg ratio has an important influence on the performance of the alloy. A high Zn / Mg ratio can effectively improve the strength of the alloy, but it will produce serious macrosegregation, increase the tendency of alloy casting hot cracks and reduce the grain size of the alloy, and damage the plasticity, toughness and corrosion resistance of the alloy. The alloy with a low Zn / Mg ratio has good plasticity and toughness, but low strength. Therefore, Zn is controlled at 7.6% to 8.4%, Mg is controlled at 1.8% to 2.3%, and Zn / Mg is controlled at 3.3 to 4.67.

[0045] Cu: 2.0%~2.6%

[0046] Cu element, as one of the main elements of alloy, has an important influence on the organization and performance of alloy. Cu element has very little solid solubility in alloy, and its main function is to increase the dispersion of precipitation phase in alloy, improve grain boundary organization structure, such as grain boundary without precipitation zone, grain boundary precipitation phase, etc. In addition, Cu element can promote the nucleation of GP zone (solute atom enriched zone), improve the aging stability of GP zone, and prevent rapid coarsening. Cu atom can also replace Zn element in η phase (MgZn2) and T phase (Al2Mg3Zn3), form AlZnMgCu quaternary phase, reduce the potential difference between alloy crystal and grain boundary, improve the corrosion resistance of alloy, when Cu content is too much, the second phase in alloy is mainly Al2MgCu and Al7Cu2Fe phase, these coarse brittle phases are broken in deformation process, easily produce stress concentration, accelerate microcrack extension, and reduce the plastic toughness of alloy. Therefore, Cu content in the present invention is controlled at 2%~2.6%.

[0047] Mn: 0.05% or less, Cr: 0.04% or less

[0048] By adding Mn and Cr elements, a dispersed phase can be formed in the alloy, which can inhibit the recrystallization of the alloy and improve the plasticity, toughness and stress corrosion resistance of the alloy. However, the dispersed phase formed by Mn and Cr is in a non-coherent relationship with the matrix. During the solution quenching process, these dispersed phases will become the heterogeneous nucleation core of the precipitation phase, forming a coarse second phase, consuming the alloy element content, reducing the aging strengthening effect, and increasing the quenching sensitivity of the alloy. Therefore, the Mn content is controlled to be below 0.05% and the Cr content is controlled to be below 0.04%.

[0049] Zr: 0.08%~0.25%

[0050] The addition of Zr element can react with the aluminum matrix to precipitate a large number of dispersed Al3Zr particles. As a hard nucleation core, Al3Zr particles can refine the alloy grains to a certain extent. The dispersed Al3Zr has a coherent relationship with the matrix and has a strong coherent strengthening effect. Compared with Cr, it is not easy to become a heterogeneous nucleation core during the solution quenching process, which can greatly reduce the quenching sensitivity of the alloy. In addition, the metastable Al3Zr particles can effectively pin dislocations, hinder the migration of alloy grain boundaries and subgrain boundaries, and then control the evolution of subgrain structure in subsequent heat treatment, inhibit the recrystallization of the alloy, retain the deformed structure in the alloy, and indirectly improve the corrosion resistance of the alloy. Therefore, the Zr content is controlled to be 0.08% to 0.25%.

[0051] Fe: 0.15% or less, Si: 0.10% or less

[0052] Fe and Si are impurity elements, which will form some hard, brittle, insoluble and coarse compounds in the alloy, such as Al7Cu2Fe, FeAl3, AlFeMnSi and Mg2Si. Under conventional heat treatment temperature, these coarse brittle phases cannot dissolve back into the matrix, and are not coherent with the matrix. They are easily broken during subsequent processing and are distributed discontinuously in the form of bands along the deformation direction. These second phases are hard and brittle phases, and their deformation tends to be inconsistent with the matrix, which will cause microcrack initiation and accelerate the crack growth rate during thermal deformation, reducing the plastic toughness of the alloy. With the increase of Fe and Si content, the coarse Al7Cu2Fe changes from rod-shaped to irregular, and with the increase of the number of Al7Cu2Fe and Mg2Si particles, the alloy will produce more PSN (particle promoted nucleation) recrystallized grains during deformation, and will not form an extruded fiber structure, which will reduce the strength of the alloy. Therefore, the Fe content is controlled to be below 0.15% and the Si content is controlled to be below 0.10%.

[0053] Ti: 0.06% or less

[0054] Ti can refine the grains of cast aluminum alloy and is a very effective grain refiner. When a small amount of Ti is added to the aluminum alloy, the aluminum alloy will form a primary Al3Ti phase during the solidification process, providing more nucleation points for the Al matrix. The secondary precipitation of Al3Ti phase helps to inhibit the growth of recrystallized grains, and the strength, toughness, wear resistance, fatigue resistance and thermal stability of the alloy are all improved. Therefore, the Ti content is controlled to be below 0.06%.

[0055] Next, a method for preparing an aluminum alloy casing is described.

[0056] S1: preparing the raw materials according to their weight percentage and preparing the tube blank through a spray deposition process;

[0057] By preparing tube blanks through spray deposition technology, the Zn content of the alloy can reach more than 8% without serious segregation, thereby improving the strength of the alloy. In addition, due to the high cooling rate of spray forming, the resulting deposited blank has uniform composition and fine grains. The second phase is distributed in a semi-continuous network at the grain boundary, while the 1-5μm spherical or short rod-shaped second phase is dispersed in the crystal. The overall distribution is relatively uniform, and the second phase at the grain boundary is similar to the second phase in the crystal.

[0058] S2: Two-stage homogenization treatment: The obtained tube blank is subjected to two-stage homogenization treatment.

[0059] Specifically, the obtained tube blank is subjected to the first stage heat treatment and the second stage heat treatment in sequence, and then naturally cooled to room temperature to obtain the tube blank subjected to double-stage homogenization treatment, wherein the temperature of the first stage heat treatment is lower than the temperature of the second stage heat treatment; wherein the temperature of the first stage heat treatment is 400-415°C, and the temperature is kept for 8-12 hours, and the temperature of the second stage heat treatment is 455-470°C, and the temperature is kept for 12-24 hours. The heating rates during the first stage heat treatment and the second stage heat treatment are both 10-20°C / min.

[0060] On the one hand, the two-stage homogenization process promotes the coarse AlZnMgCu primary phase to dissolve back into the matrix to the maximum extent, so as to reduce the difficulty of subsequent solution heat treatment, and at the same time avoid the phenomenon of over-burning caused by melting of grain boundaries due to excessive heating temperature. On the other hand, the first stage adopts a lower heat treatment temperature to promote the precipitation of fine and dense Al3Zr crystal nuclei in the alloy, and the second stage greatly eliminates the microsegregation in the matrix, promotes the growth of Al3Zr crystal nuclei, and forms more and more uniformly distributed Al3Zr particles, thereby inhibiting the alloy recrystallization behavior in subsequent hot working and solution treatment, and improving the strength and toughness of the alloy.

[0061] S3: Extrusion treatment: the tube blank that has undergone the double-stage homogenization treatment is subjected to variable-section extrusion treatment;

[0062] Specifically, the tube billet after double-stage homogenization treatment is heated to 390-420°C, kept at this temperature for 20 minutes, and then subjected to variable cross-section extrusion treatment. During the variable cross-section extrusion treatment, the extrusion ratio is greater than 18, and the extrusion speed is 30 mm / min.

[0063] S4: Two-stage solid solution treatment: The extruded tube is subjected to two-stage solid solution treatment;

[0064] Specifically, the extruded tube is subjected to the third heat treatment and the fourth heat treatment in sequence, and then cooled by water spray at a cooling rate of 30-50°C / s to obtain a tube subjected to solid solution treatment; the temperature of the third heat treatment is lower than that of the fourth heat treatment; the temperature of the third heat treatment is 450-460°C, and the temperature is kept for 1-2 hours, and the temperature of the fourth heat treatment is 470-480°C, and the temperature is kept for 1-1.5 hours. The heating rates of the third heat treatment and the fourth heat treatment are both greater than 20°C / min.

[0065] In the two-stage solution treatment process, the first stage is kept below the eutectic temperature for a period of time to fully dissolve some strengthening phases. The second stage is kept at a higher temperature for a shorter time to further dissolve other strengthening phases and increase the solubility of solute atoms while avoiding overburning of the structure. This can shorten the solution time, reduce energy consumption, and improve the solution efficiency.

[0066] S5: Aging treatment: The tube blank after solution treatment is subjected to RRA (regression reaging) treatment to obtain a high-strength heat-resistant aluminum alloy casing.

[0067] Specifically, the tube blank that has undergone solid solution treatment is subjected to the first stage, the second stage and the third stage heat treatment in sequence to obtain the aluminum alloy casing; the temperatures of the first stage and the third stage heat treatment are both lower than the temperature of the second stage heat treatment. Specifically, it is kept at 105-120°C for 24 hours, cooled to room temperature, then heated to 180-190°C for 0.5-1 hour, cooled to room temperature, then heated to 120°C for 24 hours.

[0068] RRA treatment (regression re-aging) is adopted, which includes three stages: the first stage is peak aging at a lower temperature, fine coherent or semi-coherent dispersed phases are precipitated in the grain, and coarser continuous chain particles are distributed at the grain boundaries. The second stage is short-term regression at a higher temperature. After regression treatment, the coherent or semi-coherent precipitated phases in the grain are dissolved into the solid solution, and the continuous chain precipitated phases on the grain boundaries are merged and aggregated, and are no longer continuously distributed. This grain boundary structure improves the resistance to stress corrosion and exfoliation corrosion, but the dissolution of the η′ phase in the grain greatly reduces the strength of the alloy. The third stage is re-aging at a lower temperature to reach the peak strength, and fine partially coherent η′ phases are precipitated in the grain, dispersedly distributed, and the grain boundaries are still discontinuous non-coherent precipitated phases. After RRA treatment, the following structure is formed in the alloy: a large number of fine η′ phase particles are dispersed in the grains, coarse η phase precipitates are discretely distributed at the grain boundaries, and there is a narrow grain boundary non-precipitation zone. This structure combines the advantages of peak aging and over-aging, so that the alloy can achieve the unity of high strength and good corrosion resistance. Here, η′ is a transition phase of η phase, without a fixed and definite chemical formula.

[0069] The tensile properties of the aluminum alloy casing obtained by the technical solution of the present invention are R t0.2 =550~610MPa, R m ≥630MPa, δ≥10.0. The heat resistance of the tube body is: the yield strength after heat exposure at 120°C for 500 hours is ≥385MPa. In addition, the microstructure of the tube body is mainly composed of dispersed and refined η′ and η phases.

[0070] The technical solution of the present invention is further described by the following embodiments:

[0071] Example 1

[0072] The invention discloses an ultra-high strength aluminum alloy casing, whose chemical composition comprises, by weight percentage, 8.3% of Zn, 2.2% of Mg, 2.5% of Cu, 0.01% of Cr, 0.24% of Zr, 0.02% of Mn, 0.03% of Ti, and the remainder is Al and inevitable impurities; wherein the inevitable impurities comprise 0.15% of Fe and 0.1% of Si, which account for 0.1% of the total weight of the aluminum alloy.

[0073] The manufacturing method of the above-mentioned ultra-high strength aluminum alloy casing is as follows: after the above-mentioned raw materials are spray-formed, an ingot, i.e., a tube blank, is obtained, the ingot is kept at 415°C for 12 hours, then kept at 470°C for 24 hours, a two-stage homogenization treatment is performed, and the ingot is naturally cooled to room temperature, and then kept at 420°C for 20 minutes before extrusion deformation, the extrusion ratio is greater than 18, and the extrusion speed is 3mm / s; then kept at 460°C for 2 hours, kept at 480°C for 1.5 hours, solution quenching treatment is performed, cooled to room temperature at a cooling rate of 30°C / s, and then kept at 120°C for 24 hours, 190°C for 1 hour, and 120°C for 24 hours in sequence, and cooled to room temperature after the above-mentioned regression and aging treatment to obtain the aluminum alloy casing.

[0074] The mechanical properties of the ultra-high strength aluminum alloy casing obtained by the above manufacturing method reach: tensile strength of 640MPa, yield strength of 610MPa, elongation of 11%. After exposure at 120°C for 500h, the tensile properties reach: yield strength of 430MPa.

[0075] Example 2

[0076] The invention discloses an ultra-high strength aluminum alloy casing, whose chemical composition comprises, by weight percentage, 7.6% of Zn, 1.8% of Mg, 2% of Cu, 0.01% of Cr, 0.24% of Zr, 0.02% of Mn, 0.03% of Ti, and the remainder is Al and inevitable impurities; wherein the inevitable impurities comprise 0.15% of Fe and 0.1% of Si, which account for 0.1% of the total weight of the aluminum alloy.

[0077] The manufacturing method of the above-mentioned ultra-high strength aluminum alloy casing is as follows: the above-mentioned raw materials are spray-formed to obtain an ingot, the ingot is kept at 400°C for 12 hours, then kept at 450°C for 24 hours, subjected to a two-stage homogenization treatment, naturally cooled to room temperature, and then kept at 420°C for 20 minutes before extrusion deformation, with an extrusion ratio greater than 18 and an extrusion speed of 3mm / s; then kept at 450°C for 2 hours, kept at 470°C for 1.5 hours, solution quenched, cooled to room temperature at a cooling rate of 30°C / s, then kept at 105°C for 24 hours, 190°C for 1 hour and 120°C for 24 hours in turn, cooled to room temperature after the above-mentioned regression and aging treatment, and the aluminum alloy casing is obtained.

[0078] The mechanical properties of the ultra-high strength aluminum alloy casing obtained by the above manufacturing method reach: tensile strength of 630MPa, yield strength of 590MPa, elongation of 15%. After exposure to 120°C for 500h, the tensile properties reach: yield strength of 420MPa.

[0079] Example 3

[0080] The invention discloses an ultra-high strength aluminum alloy casing, whose chemical composition comprises, by weight percentage, 8% of Zn, 2% of Mg, 2.3% of Cu, 0.02% of Cr, 0.12% of Zr, 0.01% of Mn, 0.04% of Ti, and the remainder is Al and inevitable impurities; wherein the inevitable impurities comprise 0.14% of Fe and 0.09% of Si, which account for 0.14% of the total weight of the aluminum alloy.

[0081] The manufacturing method of the above-mentioned 550MPa grade ultra-high strength aluminum alloy casing is as follows: the above-mentioned raw materials are spray-formed to obtain an ingot, the ingot is kept at 410°C for 10, then kept at 460°C for 18h, subjected to a two-stage homogenization treatment, naturally cooled to room temperature, and then kept at 420°C for 20min before extrusion deformation, the extrusion ratio is greater than 18, and the extrusion speed is 3mm / s; then kept at 455°C for 1h, kept at 475°C for 1h, solution quenched, cooled to room temperature at a cooling rate of 30°C / s, and then kept at 110°C for 24h, 190°C for 1h and 120°C for 24h in sequence, cooled to room temperature after the above-mentioned regression and aging treatment, and the aluminum alloy casing is obtained.

[0082] The mechanical properties of the ultra-high strength aluminum alloy casing obtained by the above manufacturing method are as follows: tensile strength is 636MPa, yield strength is 593MPa, elongation is 14%. After exposure to 120°C for 500h, the tensile properties reach: yield strength is 421MPa.

[0083] Example 4

[0084] The invention discloses a 550MPa-level ultra-high strength aluminum alloy casing, whose chemical composition comprises, by weight percentage, 7.8% of Zn, 1.9% of Mg, 2.1% of Cu, 0.03% of Cr, 0.17% of Zr, 0.03% of Mn, 0.04% of Ti, and the remainder is Al and inevitable impurities; wherein the inevitable impurities comprise 0.14% of Fe and 0.09% of Si, which account for 0.14% of the total weight of the aluminum alloy.

[0085] The manufacturing method of the above-mentioned 550MPa grade ultra-high strength aluminum alloy casing is as follows: the above-mentioned raw materials are spray-formed to obtain an ingot, the ingot is kept at 410°C for 10, then kept at 470°C for 18h, subjected to a two-stage homogenization treatment, naturally cooled to room temperature, and then kept at 420°C for 20min before extrusion deformation, the extrusion ratio is greater than 18, and the extrusion speed is 3mm / s; then kept at 455°C for 1h, kept at 475°C for 1h, solution quenched, cooled to room temperature at a cooling rate of 30°C / s, and then kept at 120°C for 24h, 190°C for 1h and 120°C for 24h in sequence, cooled to room temperature after the above-mentioned regression and aging treatment, and the aluminum alloy casing is obtained.

[0086] The mechanical properties of the ultra-high strength aluminum alloy casing obtained by the above manufacturing method are as follows: tensile strength is 635MPa, yield strength is 580MPa, elongation is 14%. After exposure to 120°C for 500h, the tensile properties reach: yield strength is 410MPa.

[0087] Example 5

[0088] The invention discloses a 550MPa-level ultra-high strength aluminum alloy casing, whose chemical composition comprises, by weight percentage, 8.2% of Zn, 2.1% of Mg, 2.3% of Cu, 0.02% of Cr, 0.22% of Zr, 0.01% of Mn, 0.02% of Ti, and the remainder is Al and inevitable impurities; wherein the inevitable impurities comprise 0.13% of Fe and 0.09% of Si, which account for 0.13% of the total weight of the aluminum alloy.

[0089] The manufacturing method of the above-mentioned 550MPa grade ultra-high strength aluminum alloy casing is as follows: the above-mentioned raw materials are spray-formed to obtain an ingot, the ingot is kept at 410°C for 10, then kept at 470°C for 16h, subjected to a two-stage homogenization treatment, naturally cooled to room temperature, and then kept at 420°C for 20min before extrusion deformation, the extrusion ratio is greater than 18, and the extrusion speed is 3mm / s; then kept at 450°C for 1h, kept at 470°C for 1h, solution quenched, cooled to room temperature at a cooling rate of 30°C / s, and then kept at 120°C for 16h, 190°C for 1h and 120°C for 24h in sequence, cooled to room temperature after the above-mentioned regression and aging treatment, and the aluminum alloy casing is obtained.

[0090] The mechanical properties of the ultra-high strength aluminum alloy casing obtained by the above manufacturing method are as follows: tensile strength is 638MPa, yield strength is 605MPa, elongation is 12%. After exposure to 120°C for 500h, the tensile properties reach: yield strength is 425MPa.

[0091] Example 6

[0092] The invention discloses a 550MPa-level ultra-high strength aluminum alloy casing, whose chemical composition comprises, by weight percentage, 7.7% of Zn, 2.2% of Mg, 2.4% of Cu, 0.01% of Cr, 0.09% of Zr, 0.02% of Mn, 0.02% of Ti, and the remainder is Al and inevitable impurities; wherein the inevitable impurities comprise 0.15% of Fe and 0.1% of Si, which account for 0.1% of the total weight of the aluminum alloy.

[0093] The manufacturing method of the above-mentioned 550MPa grade ultra-high strength aluminum alloy casing is as follows: the above-mentioned raw materials are spray-formed to obtain an ingot, the ingot is kept at 410°C for 10, then kept at 460°C for 18h, subjected to a two-stage homogenization treatment, naturally cooled to room temperature, and then kept at 420°C for 20min before extrusion deformation, the extrusion ratio is greater than 18, and the extrusion speed is 3mm / s; then kept at 455°C for 1h, kept at 475°C for 1h, solution quenched, cooled to room temperature at a cooling rate of 30°C / s, and then kept at 110°C for 24h, 190°C for 1h and 120°C for 24h in sequence, cooled to room temperature after the above-mentioned regression and aging treatment, and the aluminum alloy casing is obtained.

[0094] The mechanical properties of the ultra-high strength aluminum alloy casing obtained by the above manufacturing method are as follows: tensile strength is 631MPa, yield strength is 580MPa, elongation is 15%. After exposure to 120°C for 500h, the tensile properties reach: yield strength is 410MPa.

[0095] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

[0096] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. An aluminum alloy casing, characterized in that: By weight percentage, it includes Zn: 7.6% to 8.4%, Mg: 1.8% to 2.3%, Cu: 2.0% to 2.6%, Zr: 0.08%~0.25%, Cr≤0.04%, Mn≤0.05%, Ti≤0.06%, and the balance is Al and unavoidable impurities.

2. The aluminum alloy casing according to claim 1, characterized in that: The aluminum alloy casing has a tensile strength of not less than 630 MPa, a yield strength of 550-610 MPa, and an elongation of not less than 10.0%; after heat exposure at 120°C for 500 hours, the yield strength of the aluminum alloy casing is not less than 385 MPa.

3. The method for preparing an aluminum alloy casing according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1: preparing the raw materials according to their weight percentage and obtaining a tube blank through a spray deposition process; S2: subjecting the obtained tube blank to a first stage heat treatment and a second stage heat treatment in sequence to obtain a tube blank subjected to a double-stage homogenization treatment, wherein the temperature of the first stage heat treatment is lower than the temperature of the second stage heat treatment; S3: Extruding the tube blank that has undergone the double-stage homogenization treatment to obtain an extruded tube blank; S4: subjecting the extruded tube to a third heat treatment and a fourth heat treatment in sequence to obtain a tube that has undergone a solid solution treatment; wherein the temperature of the third heat treatment is lower than the temperature of the fourth heat treatment; S5: subjecting the solution treated tube blank to first, second and third stage heat treatments in sequence to obtain the aluminum alloy casing; the temperatures of the first and third stage heat treatments are both lower than the temperature of the second stage heat treatment.

4. The method for preparing an aluminum alloy casing according to claim 3, characterized in that: In step S2, the temperature of the first stage heat treatment is 400-415° C., and the temperature is kept for 8-12 hours. The temperature of the second stage heat treatment is 455-470° C., and the temperature is kept for 12-24 hours.

5. The method for preparing an aluminum alloy casing according to claim 3, characterized in that: In the step S2, the heating rates during the first stage heat treatment and the second stage heat treatment are both 10-20°C / min.

6. The method for preparing an aluminum alloy casing according to claim 3, characterized in that: During the variable cross-section extrusion process, the extrusion ratio is greater than 18 and the extrusion speed is 30 mm / min. Before the variable cross-section extrusion process, the tube blank that has undergone the double-stage homogenization treatment is heated to 390-420° C. and kept warm for 20 minutes before the variable cross-section extrusion process is performed.

7. The method for preparing an aluminum alloy casing according to claim 3, characterized in that: In step S4, the temperature of the third stage heat treatment is 450-460° C., and the temperature is kept for 1-2 hours. The temperature of the fourth stage heat treatment is 470-480° C., and the temperature is kept for 1-1.5 hours.

8. The method for preparing an aluminum alloy casing according to claim 7, characterized in that: The heating rates of the third stage heat treatment and the fourth stage heat treatment are both greater than 20° C. / min.

9. The method for preparing an aluminum alloy casing according to claim 3, characterized in that: In step S5, the first stage heat treatment temperature is 105-120°C, and the heat preservation is 24 hours. The second stage heat treatment temperature is 180-190°C, and the heat preservation is 0.5-1 hour. The third stage heat treatment temperature is 120°C and the heat preservation is 24 hours.

10. Use of the aluminum alloy casing according to any one of claims 1 to 2 in the field of oil and gas exploration and development.